Strangers in a Strange Land - Brlek, Tomislav (Array, 1998)
Starting with the biblical episode of the exodus and the multifold implications of the theme of exile as developed in the writings of Derrida and Brodsky a cursory analysis of the construction of identity in a foreign context in the works of four exemplary exiled modern writers (James Joyce, T.S. Eliot, Ezra Pound, Samuel Beckett) is offered.